Characterization of Aedes sp. larvae: Detection of dengue, Japanese encephalitis and West Nile virus with knockdown resistance mutations in Mulyorejo, Surabaya, Indonesia - Adelia Gita Prasasti; Teguh Hari Sucipto; Muhammad Ridho Hafid Kurniawan; Shifa Fauziyah; Anak Agung Istri Dalem Cinthya Riris; Yohana Djurumana; Nafisah Nurul Hapsari; Neni Isna Farihah; Alvia Rachma Wijayanti; Nita Kusumawati; Hariyono Hariyono; Puspa Wardhani (Universitas Nahdlatul Ulama Surabaya, 2026)
Indonesia recorded the highest dengue mortality rate in Asia in 2022, with 45,387 cases and 432 deaths. This study aimed to investigate the coexistence of arboviruses and insecticide resistance mechanisms in Aedes vectors mosquitos’ populations in Mulyorejo District, Surabaya, during the early monsoon season of 2021. A cross-sectional survey was conducted in January 2021, and Aedes larvae were collected and reared to adulthood under laboratory conditions. A total of 309 Aedes larvae (comprising 65% Aedes aegypti and 35% Aedes albopictus) were collected from 36 breeding sites, identified, and georeferenced using QGIS software. RNA extraction and RT-PCR assays were performed to detect Dengue virus (DENV), Japanese encephalitis virus (JEV), West Nile virus (WNV), and knockdown resistance (KDR) mutations. Results showed seven samples positive for DENV-2 and seven for JEV, with two samples (codes 9 and 12) exhibiting co-infection with both viruses, while no WNV was detected. The detection of JEV in Aedes larvae is a notable finding, suggesting a potential secondary vector role for these species in the study area, as Culex mosquitoes are the primary vectors of JEV. Mutations at codons 1016 (V1016G) and 1534 (F1534C), associated with pyrethroid and DDT resistance, were detected in eight and seven samples, respectively. These findings confirm the circulation of DENV-2 and JEV in local Aedes populations, highlighting the presence of KDR mutations that confer insecticide resistance. The results underscore the urgent need for integrated vector management in Surabaya, combining arbovirus surveillance, insecticide resistance monitoring, and community-based source reduction to mitigate arboviral disease transmission.